2014
DOI: 10.4236/ijcns.2014.712052
|View full text |Cite
|
Sign up to set email alerts
|

Proxy Server Experiment and Network Security with Changing Nature of the Web

Abstract: The total reliance on internet connectivity and World Wide Web (WWW) based services is forcing many organizations to look for alternative solutions for providing adequate access and response time to the demand of their ever increasing users. A typical solution is to increase the bandwidth; this can be achieved with additional cost, but this solution does not scale nor decrease users perceived response time. Another concern is the security of their network. An alternative scalable solution is to deploy a proxy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The study reported in Reference 7 describes an experiment to evaluate the efficiency of proxy servers and the security they offer. Authors are particularly curious in portraying the evolving nature of the web, which has been impacted through the functionality of proxy servers and the level of protection they offered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study reported in Reference 7 describes an experiment to evaluate the efficiency of proxy servers and the security they offer. Authors are particularly curious in portraying the evolving nature of the web, which has been impacted through the functionality of proxy servers and the level of protection they offered.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed study of IDS can be found in Reference 9. As discussed in the References 7‐9, proxy servers, firewalls, and IDS also could not cope with the dynamic threats. In other context, Proxy servers like Virtual Private Networks (VPNs) and firewalls are centralized systems records issues in terms of network connection and minimal possibility of backup, but there is no graceful degradation of the system.…”
Section: Introductionmentioning
confidence: 99%